Microstructured organic ferroelectric thin film capacitors by solution micromolding - Lenz, Thomas; Zhao, Dong; Richardson, George; Katsouras, Ilias; Asadi, Kamal; Glaßer, Gunnar; Zimmermann, Samuel T.; Stingelin, Natalie; Roelofs, W. S. Christian; Kemerink, Martijn; Blom, P. W. M.; Leeuw, Dago M. de (Physica status solidi. A, Applications and materials science, 2015)
Ferroelectric nanostructures offer a promising route for novel integrated electronic devices such as non-volatile memories. Here we present a facile fabrication route for ferroelectric capacitors comprising a linear array of the ferroelectric random copolymer of vinylidenefluoride and trifluoroethylene (P(VDF-TrFE)) interdigitated with the electrically insulating polymer polyvinyl alcohol (PVA). Micrometer size line gratings of both polymers were fabricated over large area by solution micromolding, a soft lithography method. The binary linear arrays were realized by backfilling with the second polymer. We investigated in detail the device physics of the patterned capacitors. The electrical equivalent circuit is a linear capacitor of PVA in parallel with a ferroelectric capacitor of P(VDF-TrFE). The binary arrays are electrically characterized by both conventional Sawyer-Tower and shunt measurements. The dependence of the remanent polarization on the array topography is explained by numerical simulation of the electric field distribution.
Gesehen am 05.12.2019